2008
DOI: 10.1055/s-2007-1004541
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Gene Polymorphisms in Premenopausal Women with Major Depression

Abstract: Glucocorticoid receptor gene polymorphisms are associated with glucocorticoid hypersensitivity and visceral obesity. Perturbations in HPA axis sensitivity to glucocorticoids implicated in the pathogenesis of major depression may result from functional alterations in the glucocorticoid receptor gene. We 1) examined the prevalence of genotype distribution of specific polymorphisms of the glucocorticoid receptor gene (Bcl1, N363S, rs33388, rs33389) in a subset of women from the P.O.W.E.R. Study (which enrolled 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 15 publications
8
33
0
Order By: Relevance
“…In accordance with the finding of others we observed a slight increase of IAT in depressed patients (Eskandari et al, 2005;Everson-Rose et al, 2009;Greggersen et al, 2011;Kim et al, 2011a,b;Krishnamurthy et al, 2008;Ludescher et al, 2008;Weber-Hamann et al, 2002;Williams et al, 2009). IAT is seen as a risk factor for the development of the metabolic syndrome and type 2 diabetes mellitus, and may link depression to cardio-metabolic disorders (Alexopoulos et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with the finding of others we observed a slight increase of IAT in depressed patients (Eskandari et al, 2005;Everson-Rose et al, 2009;Greggersen et al, 2011;Kim et al, 2011a,b;Krishnamurthy et al, 2008;Ludescher et al, 2008;Weber-Hamann et al, 2002;Williams et al, 2009). IAT is seen as a risk factor for the development of the metabolic syndrome and type 2 diabetes mellitus, and may link depression to cardio-metabolic disorders (Alexopoulos et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In detail, enlarged adrenal gland volume has been found in three case-control studies (Kessing et al, 2011), and most although not all cross-sectional studies have reported increased volumes of intra-abdominal adipose tissue in patients with major depression using imaging technology (Eskandari et al, 2005;Everson-Rose et al, 2009;Greggersen et al, 2011;Kim et al, 2011a,b;Krishnamurthy et al, 2008;Ludescher et al, 2008;Weber-Hamann et al, 2002;Williams et al, 2009). One study reported increased PAT in depression so far .…”
Section: Introductionmentioning
confidence: 96%
“…The SNP at rs41423247 is located in intron B, 647 bp downstream of exon 2, and results in a guanine to cytosine alteration (Derijk, 2009). The direction of the results of our study conform to previous research reporting an association between rs41423247 and increased sensitivity to glucocorticoids following a DEX-CRH test, lower cortisol response after psychological stress (Derijk, 2009;Manenschijn et al, 2009), and major depression disorder (Krishnamurthy et al, 2008;Kumsta et al, 2007). The mechanism by which this SNP exerts its effect remains unclear because it is not located in a coding, regulatory or splicing part of GR.…”
Section: Discussionsupporting
confidence: 88%
“…The rs41423247 polymorphism might affect the GR gene promoter by selectively acting on repressor or enhancer sites within the promoter, thereby altering GC sensitivity [39]. Previous studies have reported an association between SNP and increased sensitivity to glucocorticoids following a DEX-CRH test, a lower cortisol response after psychological stress [40,41], and more traumatic memories and major depressive disorders [28,42]. Hauer et al [28] observed that individuals who were homozygous carriers of the minor (G) allele of the SNP had more traumatic memories and lower plasma cortisol levels, and were at increased risk for development of PTSD symptoms after cardiac surgery, while homozygous G allele carriers had enhanced GR sensitivity and an increased number of GRs, which was a strong predictor of the presence of PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%